Resisting Borders: Transnational Cartographies in US Latinx Studies - García-Avello, Macarena (International Journal of English Studies, 2021)
This article examines the evolution of the borderlands as an organizing trope by focusing on how the transcendence beyond cultural nationalist perspectives traces the shift from Chicano/a to Latinx discourses. In order to address this issue, I will analyse two twenty-first-century Latinx texts that delve into the intricate ways in which transnational forces collide with economic, cultural and political processes that persistently revolve around the framework of the nation-state: Alicia Gaspar de Alba´s Desert Blood: The Juarez Murders (2005) and Maya Chinchilla´s The Cha Cha Files: A Chapina Poética (2014). The corpus of works selected will focus on the political readings derived from textual negotiation with a changing political, social and economic reality. This results in constant tensions between globalising processes, worldwide interconnectedness and transnational interactions, on the one hand, and the regulatory power of the state, on the other.